2019
DOI: 10.3390/electronics8101153
|View full text |Cite
|
Sign up to set email alerts
|

Airborne LiDAR Point Cloud Filtering by a Multilevel Adaptive Filter Based on Morphological Reconstruction and Thin Plate Spline Interpolation

Abstract: Point cloud filtering is a crucial step in most airborne light detection and ranging (LiDAR) applications. Many filtering algorithms have been proposed, but the filtering effect has some limitations in complex environments. To improve the filtering effect in complex terrain, a multilevel adaptive filter (MAF) combining morphological reconstruction and thin plate spline (TPS) interpolation is proposed. The digital elevation model (DEM) generated in each iteration is used as the marker image for morphological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…In previous works, e.g., [19,28,[67][68][69], it was found that noise reduction during preprocessing yielded a better digital terrain model, but on the other hand this procedure could sometimes reduce the accuracy of the model, as [70] found in their study. We had a hypothesis that the noise reduction of the point cloud results in more accurate models in our case, and we pointed out that different noise reduction techniques can have a significant effect on the input data which are the basis of the next stage of the process, i.e., ground point classification.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In previous works, e.g., [19,28,[67][68][69], it was found that noise reduction during preprocessing yielded a better digital terrain model, but on the other hand this procedure could sometimes reduce the accuracy of the model, as [70] found in their study. We had a hypothesis that the noise reduction of the point cloud results in more accurate models in our case, and we pointed out that different noise reduction techniques can have a significant effect on the input data which are the basis of the next stage of the process, i.e., ground point classification.…”
Section: Discussionmentioning
confidence: 71%
“…Besides the fixed kernel windows, other robust methods exist, including the iterative multiscale spline, which was developed directly for densely forested areas [25]. Furthermore, [26] used a progressive morphology, [27] used a segmentation-based robust interpolation, and [28] used a combination of a multilevel adaptive filter (MAF) with morphological reconstruction and a thin plate spline (TPS) interpolation algorithm for the classification procedure to extract more precisely the bare earth. In addition, nowadays, there is an increasing number of easy-to-use algorithms which are implemented in freely available software to help for the users with the filtering process.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, many ground filtering methods have been proposed to separate ground points from point clouds. According to the filtering strategies used, these methods can be grouped into five primary categories: interpolation-based [13][14][15][16][17][18][19][20][21][22][23][24][25][26], slope-based [27][28][29][30][31][32][33], morphological-based [34][35][36][37][38][39][40], segmentation-based [41][42][43][44][45][46][47][48][49], and simulation-based [50][51][52][53] approaches. Each category has shown its advantages in dealing with different kinds of topography.…”
Section: Introductionmentioning
confidence: 99%
“…The capturing distance of Airborne Laser Scanning (ALS) is relatively consistent and the sampling density is much sparser. Considering limitation of scanning degree and flight elevation, ALS point clouds are commonly processed as 2.5D data for filtering and typical methods mainly include mathematical morphology (Li et al, 2013;Li et al, 2017;Meng et al, 2019), surface interpolation (Hu et al, 2014), segmentation (Chen et al, 2016), etc., which are discussed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Curved surface-based methods perform better to preserve sharp details and conform terrain relief. Least-square, Thin-Plate-Spline (TPS) (Meng et al, 2019), and scanline spline (Martí nez Sá nchez et al, 2019) are commonly used to fit the surface while accurate interpolation points are strictly required for reasonable fitting. Improvements involve seed point selection such as moving-window weighted iterative least-squares fitting (Qin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%